Peristrophe bicalyculata extract and quercetin ameliorate high fat diet- streptozotocin-induced type ii diabetes in Wistar rats - Iwara Arikpo Iwara; Eve Ofonime Mboso; Ofem Effiom Eteng; Kelvin Ngwu Elot; Godwin Oju Igile; Patrick Ekong Ebong (Elsevier, 2022)
Aim: Diabetes mellitus and its related complications lead to various systemic alterations. This study aimed to evaluate the effect of the administration of extract of Peristrophe bicalyculata (PB) and quercetin on diabetic rat models. Method: Forty-eight albino rats (120-150 g) were divided into six groups of 8 animals each. The groups included normal and diabetic control (NC and DC (placebo)), Quercetin (10 mg/kg b.w.), Metformin, low (250 mg/kg b.w.) and high-dose PB (500 mg/kg b.w.), were administered for 21 days. Result: Administration of PB extracts, quercetin and metformin recorded a significant anti-diabetic activity and increase in body weight compared to DC. Results of hepato-toxicity recorded in diabetic control groups were favourably ameliorated in diabetic treated groups. Changes were observed in RBC and its parameters (HGB, MC, HCT and MCHC), and PLT in treated groups compared to DC. Gas Chromatography-Mass Spectroscopy analysis revealed the presence of n-hexadecanoic acid, oleic acid, octadecanoic acid and 9-octadecenal in the extract. Conclusion: the result from this study revealed extract PB and quercetin to possess the anti-diabetic activity and possibly indicating this drug may be an alternative to manage this disorder and its related complications.